Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Pada Siswa Sekolah Dasar - Hakiki, Nurul; Kaharuddin, Kaharuddin; Rahmat, Yusran (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The primary aim of this study was to examine the impact of the Jigsaw cooperative learning model on the learning outcomes of Social Studies (IPS) among fifth-grade students at SDN 148 Bonto Bulaeng, Kabupaten Bulukumba. This research adopted a pre-experimental design, specifically a quasi-experimental design, and utilized a quantitative approach. A sample of 12 students was selected for the study. Data collection was conducted through learning outcome tests and observation sheets, while data analysis employed descriptive analysis and T-Test statistical methods. The findings revealed a significant improvement in the students' Social Studies learning outcomes post-implementation of the Jigsaw cooperative learning model. Initially, the average pretest score was 59, which increased to an average posttest score of 83. The T-Test analysis further confirmed the positive effect of the Jigsaw model on learning outcomes, with a significance value of 0.010, which is below the alpha value of 0.05 (0.010 < 0.05). Thus, the study concluded that the Jigsaw cooperative learning model significantly enhances learning outcomes in Social Studies for fifth-grade students, leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1).